Study of the influence of viruses of the family Herpesviridae 4, 6 types and human endogenous retroviruses on the course of multiple sclerosis - Kolyada, Oleg; Kuchma, Iryna; Kolyada, Tetyana; Sklyar, Anatoly; Tynynyka , Lyudmila (Annals of Mechnikov’s Institute, 2023)
Introduction. During the last decades, the hypothesis about the key pathogenetic role in the development of multiple sclerosis (MS) of viruses of the Herpesviridae family and human endogenous retroviruses (HERV) has been increasingly confirmed. The study of the relationship between the state of cytokinesis and the activity of MS, as well as the type of disease course is one of the topical areas of research into the immunopathogenesis of MS since cytokines are key factors in the development of inflammation in the central nervous system (CNS). The heterogeneity of the disease suggests that MS is not caused or triggered by a single virus, but a combination of them may act as a trigger in genetically susceptible individuals. The aim of our work was to establish the role of EBV and HHV-6 infections and endogenous retroviruses HERV-W in the pathogenesis of multiple sclerosis, which is mediated by their participation in the exacerbation and progression of the disease by affecting the systemic response of cytokines. Materials and methods. An examination of 98 patients registered in the Department of Neuroinfections and Multiple Sclerosis of the National Institution "Institute of Neurology, Psychiatry and Narcology of the National Academy of Medical Sciences of Ukraine" were carried out. The criterion for inclusion in the study was the presence of a verified diagnosis of "multiple sclerosis" in accordance with the order of the Ministry of Health of Ukraine No. 487, August 17, 2007 (code G35 according to ICD-10). Depending on the activity of the disease, the following subgroups were formed: MS(R1) - a subgroup of patients with relapsing-remitting type of MS (RRMS) in the exacerbation stage (clinical and radiological activity), n=24. MS(R2) - a subgroup of patients with relapsing-remitting type of MS in the stage of clinical and radiological remission, n=42. MS(P1) - a group of patients with progressive types of MS (PMS) with steady progression, n=21. MS(P2) - a group of patients with progressive types of MS at the stage of stabilization, n=11. The control group consisted of 27 practically healthy individuals, the inclusion criteria of which were the absence of acute infections for at least 1 month before the examination, the absence of chronic inflammatory, allergic, and autoimmune diseases. Immunological studies were carried out in the laboratory of clinical immunology and allergology of the National Institution "Mechnikov`s Institute of Microbiology and Immunology of National Academy of Sciences of Ukraine". Determination of the content of IgM and IgG to the nuclear antigen of EBV (EBNA1) and HHV-6, the levels of IFN-γ, IL-1β, IL-10, IL-12 and glycoprotein HERV-W in blood serum was carried out by the method of solid-phase enzyme-linked immunosorbent assay (ELISA) with using test systems certified in Ukraine. Determination of EBV and HHV-6 DNA in blood serum was carried out by polymerase chain reaction (PCR). Statistical processing of the obtained data was carried out using the program STATISTICA 11.0 (StatSoft, Inc) and XLSTAT 19.6 (Addinsoft). Spearman’s correlation analysis was used to determine the relationship between phenomena. Results and discussion. The analysis of clinical data of patients with different types of the course of MS showed differences in indicators important in prognostic terms, such as the severity and duration of onsets, the degree of disability, the completeness and duration of clinical remissions, the frequency and duration of relapses, the peculiarities of the course with various neurological syndromes that occur in genetically predisposed person as a result of the action of one or more environmental factors. The presence of specific IgG to EBNA1 and HHV-6 was revealed, as well as the qualitative and quantitative determination of the DNA of these viruses in the blood serum of patients with multiple sclerosis in comparison with control group depending on the clinical course of the disease as a result of the screening of persistent viral infections initiated with the development of MS and the response of the body’s immune system. The presence of EBV and HHV-6 DNA in blood serum indicated the activation of the viruses and the lytic stage of the infection. All groups of the study patients were divided into groups of seropositive and seronegative individuals to determine the relationship between the presence of IgG to HHV-6 in blood serum and markers of inflammation: the levels of IL-1β, IFN-γ, and IL-12 were increased in 18; 2,4; 2,4 times, respectively, compared to the control group in seropositive patients. Based on studies of the levels of IL-1β, IFN-γ, IL-12, and IL-10 cytokines, it was shown that the content of the anti-inflammatory cytokine IL-10 in the MSHHV-6+ group was reduced by half compared to the level in healthy individuals. It was shown that the relationship between serum IgG to EBNA1 and clinical indicators and levels of cytokines in patients with MS varies depending on the form of illness, stage and course of MS due to the strong correlation between serum IgG to EBNA-1 and levels of cytokines. A study of the cytokine profile of blood serum revealed pro-inflammatory activation of the regulatory component of humoral immunity in both patients with PMS and patients with RRMS in the acute stage, as evidenced by significantly increased levels of IL-1β. It was demonstrated that the content of HERV-W glycoprotein in the blood serum was higher in the group of patients with steady progression of MS and correlated with the clinical course of the disease and Expanded Disability Status Scale (EDSS) at the studying the level of HERV-W glycoprotein in the blood serum of patients with different types of course and activity of MS. This suggests that the influence of endogenous retroviruses on the pathogenesis of multiple sclerosis is realized through the support of inflammatory conditions that nourish the autoimmune disorder. Conclusions. The relationship between a high level of viral load based on the content of specific IgG to EBNA1 and HHV-6 and the number of EBV and HHV-6 DNA copies in the blood serum of MS patients with the progressive type of the course of the disease in comparison with the relapsing-remitting type has been proven. A temperate correlation of the positivity index for IgG to EBNA1 with IL-1β and a temperate inverse correlation with IL-10 were observed in all studied groups of MS patients, except for the P2 group, which can be considered as evidence of a relationship between viral reactivation in the context of a pro-inflammatory cytokine profile. It was established that seropositive patients with MS for IgG EBV and IgG HHV-6 was more common in the progressive course of the disease and have high levels of cytokines IL-1β and IFN-γ compared to seronegative ones, and levels of IL-10, on the contrary, was lower. The concentration of HERV-W glycoprotein was also significantly higher in all groups of MS patients compared to the control group and correlated with the clinical course of the disease and the level of disability according to the EDSS scale, which indicates the significant importance of endogenous retroviruses in the pathogenesis of multiple sclerosis. The data obtained allow us to conclude that EBV infection and HHV-6 and retroviruses play an important role in the pathogenesis of multiple sclerosis, participating in the exacerbation and progression of the disease by affecting the systemic response of cytokines. Keywords: Herpesviridae 4, 6 types, human endogenous retroviruses, multiple sclerosis